The response of Antarctic sea ice algae to changes in pH and CO2 - Andrew McMinn; Muller, MN; Martin, A; Ryan, KG (2014)
Ocean acidification substantially alters ocean carbon chemistry and hence pH but the effects on sea ice formation and the CO 2 concentration in the enclosed brine channels are unknown. Microbial communities inhabiting sea ice ecosystems currently contribute 10–50% of the annual primary production of polar seas, supporting overwintering zooplankton species, especially Antarctic krill, and seeding spring phytoplankton blooms. Ocean acidification is occurring in all surface waters but the strongest effects will be experienced in polar ecosystems with significant effects on all trophic levels. Brine algae collected from McMurdo Sound (Antarctica) sea ice was incubated in situ under various carbonate chemistry conditions. The carbon chemistry was manipulated with acid, bicarbonate and bases to produce a pCO 2 and pH range from 238 to 6066 μatm and 7.19 to 8.66, respectively. Elevated pCO 2 positively affected the growth rate of the brine algal community, dominated by the unique ice dinoflagellate, Polarella glacialis . Growth rates were significantly reduced when pH dropped below 7.6. However, when the pH was held constant and the pCO 2 increased, growth rates of the brine algae increased by more than 20% and showed no decline at pCO 2 values more than five times current ambient levels. We suggest that projected increases in seawater pCO 2 , associated with OA, will not adversely impact brine algal communities.